Neanderthal activity and resting areas from stratigraphic unit 13 at the Middle Palaeolithic site of Oscurusciuto (Ginosa - Taranto, Southern Italy). (1st August 2019) - Spagnolo, Vincenzo; Marciani, Giulia; Aureli, Daniele; Berna, Francesco; Toniello, Ginevra; Astudillo, Fernando; Boschin, Francesco; Boscato, Paolo; Ronchitelli, Annamaria
Abstract: Stratigraphic Unit 13 of Oscurusciuto Rockshelter (Ginosa, Taranto, Southern Italy) is a short Mousterian palimpsest representing the first stable occupation of the site soon after the deposition of a thick layer of tephra (Mt. Epomeo Green Tuff - Ischia datable around 55 kya BP). Different activities were identified by integrating the study of lithic finds, faunal remains, and the microarchaeology of combustion features. Additionally, geo-statistical analysis of these data has been carried out using a specifically designed geodatabase within a GIS platform. Our results produced an articulated picture of this Neanderthal site as a tripartite location made of spatially segregated and integrated activity areas. A hearths' alignment (parallel to the rockshelter wall) divides the settled area into an inner and outer part. The inner part, between the hearths and the shelter wall, displays an abrupt rarefaction of the anthropic finds and was interpreted as a possible sleeping/resting area. In the outer part, several multipurpose activity areas have been identified, mostly associated with the combustion features. The Northern sector of the settlement appears devoted particularly to lithic production (to a lesser degree, activities related with lithic tools use and faunal processing took place). In the Southern sector the main activities carried out represent more intensive production and use of lithic tools and the butchering and consumption of animal resources. Additionally, in this sector evidence of space maintenance behaviour (cleaning up of working areas and refuse dumping) has been attested. Highlights: A short-term palimpsest is analysed with a spatial and multidisciplinary approach. Tripartite structure with spatially segregated and integrated activity areas. Different kind of domestic activity areas related with hearths. Possible sleeping/resting area. Preventive maintenance: cleaning-up of working areas and refuses disposal behaviour.